Hubungan Antara Pola Kuman dengan Mortalitas pada Pasien Pneumonia di IPI RS. HAM Medan - Nadia, Agnes; Bihar, Syamsul; Syarani, Fajrinur (YCMM, 2025)
Pneumonia is one of the leading causes of morbidity and mortality, partIPIlarly in hospital settings. Identifying bacterial patterns and antibiotic resistance is essential to determine appropriate therapy and reduce mortality rates. This study aimed to examine the association between bacterial patterns, antibiotic resistance, and mortality in pneumonia patients. A retrospective design was used by analyzing medical record data of pneumonia patients treated in 2022. A total of 66 patients who met the inclusion criteria were included in the analysis. Data included sputum culture results, antibiotic resistance profiles, and patient mortality status. The results showed that the most commonly found bacteria were Klebsiella pneumoniae (31.8%), followed by Acinetobacter baumannii (25.8%) and Pseudomonas aeruginosa (16.7%). The highest resistance rates were observed for meropenem (31.8%) and levofloxacin (28.8%). Statistical analysis revealed a significant association between antibiotic resistance and patient mortality (p = 0.017). However, no significant association was found between the type of causative bacteria and mortality (p = 0.414). These findings indicate that antibiotic resistance plays a major role in clinical outcomes of pneumonia patients. Therefore, regular monitoring of bacterial and resistance patterns and the implementation of rational antibiotic use policies are essential to reduce pneumonia-related mortality in hospitals.